Drug-Eluting Stents and Balloons—Materials, Structure Designs, and Coating Techniques: A Review - I. Rykowska; I. Nowak; R. Nowak (Molecules, 2020)
Controlled drug delivery is a matter of interest to numerous scientists from various domains, as well as an essential issue for society as a whole. In the treatment of many diseases, it is crucial to control the dosing of a drug for a long time and thus maintain its optimal concentration in the tissue. Heart diseases are particularly important in this aspect. One such disease is an obstructive arterial disease affecting millions of people around the world. In recent years, stents and balloon catheters have reached a significant position in the treatment of this condition. Balloon catheters are also successfully used to manage tear ducts, paranasal sinuses, or salivary glands disorders. Modern technology is continually striving to improve the results of previous generations of stents and balloon catheters by refining their design, structure, and constituent materials. These advances result in the development of both successive models of drug-eluting stents (DES) and drug-eluting balloons (DEB). This paper presents milestones in the development of DES and DEB, which are a significant option in the treatment of coronary artery diseases. This report reviews the works related to achievements in construction designs and materials, as well as preparation technologies, of DES and DEB. Special attention was paid to the polymeric biodegradable materials used in the production of the above-mentioned devices. Information was also collected on the various methods of producing drug release coatings and their effectiveness in releasing the active substance.